Performance evaluation of Moringa oleifera seeds aqueous extract for removing Microcystis aeruginosa and microcystins from municipal treated-water - Alhaithloul, Haifa A. S.; Mohamed, Zakaria A.; Saber, Abdullah A.; Alsudays, Ibtisam Mohammed; Abdein, Mohamed A.; Alqahtani, Mesfer M.; AbuSetta, Noha G.; Elkelish, Amr; Pérez, Leonardo Martín; Albalwe, Fauzeya Mateq; Bakr, Asmaa A. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Toxic microcystins (MCs) produced by cyanoprokaryotes -particularly by the cosmopolitan cyanobacterium Microcystis aeruginosa- pose adverse effects on aquatic organisms and their ecosystem and may also cause serious impacts on human health. These harmful monocyclic heptapeptides are the most prevalent cyanotoxins reported in freshwaters and must be eliminated for avoiding MCs release in receiving water bodies. Hence, this work aimed to test the efficacy of Moringa oleifera seeds water-based extract (MO) as a natural coagulant for removing cyanobacteria (especially M. aeruginosa), microalgae, and its associated MCs from pre-treated municipal wastewaters. Methodology: Four different MO coagulant doses (25, 50, 75 and 100 mg L−1) were investigated for cyanobacteria and microalgae removal by conventional coagulation assays and morphology-based taxonomy studies. Additionally, water turbidity and chlorophyll a (Chl a) content were also determined. Further, the presence and concentration of MCs soluble in water, remaining in the particulate fraction, and flocculated within the residual sludge were assessed using high-performance liquid chromatography coupled with diode array detection (HPLC-DAD). Results: The treatment with MO at 100 mg L−1 substantially reduced the number of cyanobacterial and microalgal species in the treated samples (average removal rate of 93.8% and 86.9%, respectively). These results agreed with a ∼44% concomitant reduction in Chl a and ∼97% reduction in water turbidity (a surrogate marker for suspended solids content). Notably, MCs concentrations in the treated water were significantly lowered to 0.6 ± 0.1 µg L−1 after addition of 100 mg L−1 MO. This value is below the WHO recommended limits for MCs presence in drinking water (<1.0 µg L−1). Discussion: The present study provides promising insights into the applicability of MO as a cost-effective, reliable, and sustainable natural coagulant, particularly for using in developing countries, to eliminate harmful cyanobacteria and cyanotoxins in municipal water treatment facilities.